CLINICAL AND HISTOLOGICAL CHARACTERIZATION OF ORAL PEMPHIGUS LESIONS IN PATIENTS - J.A. Rizaev; O.S. Imamov; G.Sh. Toxtayev (Central Asian Journal of Medicine, 2025)
Pemphigus is a rare group of life threatening mucocutaneous autoimmune blistering diseases. Frequently, oral lesions precede the cutaneous ones. This study aimed to describe clinical and histological features of oral pemphigus lesions in patients attending. In addition, the study aimed to assess the diagnostic significance of routine histolopathology along biopsy specimens in patients with oral pemphigus.